HYPERTENSION IN CHILDREN WITH NEPHROTIC SYNDROME - FRANKUL, FARiS M.; Fahmi, Nariman; Ahmed, Lana (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Hypertension occurs in some patients with primary nephritic syndrome it may be mediated by changes in vasopressin activities or intravascular volume. Aim of study: is to find out how many patients with idiopathic nephritic syndrome hare hypertension. Subj. & Methods: The study included 50 children (29 males and 21 females) with age ranger between 1- 13 years. Sixteen patients (32%) were with initial attack of nephritic syndrome, while thirty four patients (68%) presented with relapse. Results: Nine (18%) patients had hypertension, eight (16%) patients were relapse cases, and one (2%>) patient was with initial attack. Hypertension was found in four (8%) patients with steroid resistant neurotic syndrome, three (6%) patients with steroid sensitive nephritic syndrome in relapse state and two (4%) patients with steroid dependent nephritic syndrome. Abnormal renal function was found in four patients (8%), two (4%) with hypertension and two (4%) without hypertension. It is concluded the necessity of the follow up and periodical measurement of blood pressure of nephritic patients to allow early recognition and management of hypertension. Conclusion: the necessity of the follow up & periodical measurement of blood pressure of nephroticpatients to allow early recognition & management of hypertension.